PERLINDUNGAN HUKUM TERHADAP JABATAN NOTARIS BERKAITAN DENGAN ADANYA DUGAAN MALPRAKTEK DALAM PROSES PEMBUATAN AKTA OTENTIK - Oka Diatmika, I Gusti Agung; Atmadja, I Dewa Gde; Sri Utari, Ni Ketut (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 2 No 1 (2017), 2017)
A notary is a public officer who given sufficient authority by the state to make an authentic deed. If a party feels aggrieved over the deed of a Notary, then the party can sue the notary with the charges of malpractice in an authentic deed, although the notary has been working in accordance with the standards of an authentic deed. On this basis, it is need a legal protection for the notary, in this case, made ??by the Notary Honorary Council (MKN) as provided for in the Article 66 of paragraph (1) of Law No. 2 of 2014 on the Amendment of Law Number 30 of Year 2004 on the Notary Position (UUJN-P). There are no certain regulations on MKN positions and the kinds of legal protection given by the MKN to the notary, giving rise to legal issues namely, what the standards or requirements in the process of making an authentic deed and what the legal protection of the Position of Notary in relations to the allegations of malpractice in the making of authentic deeds. This thesis research is a normative legal research, which departed from the vacuum of norm. The legal materials collection techniques used were the study of literature and the card system. The analysis of the legal materials was conducted by using descriptive techniques, interpretations and arguments associated with the theories and concepts of law which relevant to the issues. The research findings of the problem under study, namely, that in making authentic deeds, notary must always pay attention to the validity of the agreement according to the terms of Article 1320 of the Civil Law (the Civil Codes), the requirement of making authentic deeds (Civil Code of 1868), Law on the Notary Position, as well as the Notary Code of Ethics. While MKN position as the Administrative agencies should be established in the regions of (city or regencies) in order that MKN can quickly respond to the case and provide an appeal to the parties who are not satisfied with the decision of MKN.